Decorated ceiling of the Suhaveshwar Temple - Temples of India Project Team (Jio Institute, 2024)
The moulding details and the ornamentation of the concentric circles of the ceiling of the Suhaveshwar Temple are pictured here. The lowermost moulding has bharvahakas (load bearers) and sculptures on brackets, depicting that they bear the load. Individual circles of the ceiling are made up of semi-circular fractals.